Impact of policies restricting advertising, promotion and sponsorship of sugar-sweetened beverages. Systematic Review - Guarnieri, Leila (2023)
Objective.  To assess the impact of the implementation of a ban on advertising, promotion and sponsorship (PPP) of sugar-sweetened beverages (SSBs) in terms of reducing consumption, advertising exposure and relevant clinical outcomes. Material and methods A systematic review of studies published between 2001 and 2021 was conducted using the in PubMed, Embase and LILACS databases. Experimental, observational studies and economic models written in English, Portuguese or Spanish were included. Results. Sixteen studies out of 840 identified were selected. Due to outcomes heterogeneity, a meta-analysis was not possible. The interventions included comprehensive policies, general SSBs PPP restriction policies,TV advertising, promotional, point-of-sale, and school restrictions. Clinical outcomes (such as obesity, cardiovascular disease, diabetes, and cancer), economic outcomes (such as purchase, sale, cost-effectiveness, and other economic outcomes), changes in exposure, consumption, and other measures of effectiveness were assessed. Most effect measures showed decreases following the interventions. Conclusions. Policies that include PPP restrictions on SSBs can be effective in reducing consumption, especially among children and adolescents, and have a positive impact on their health.